Disseminated tuberculosis in a child during the COVID-19 pandemic: a case report and literature review - Weng, Taoping; Dong, Yaqiong; Huang, Niwen; Zhao, Chenqu; Zhang, Lei; Cao, Shan; Tang, Jing; Zhang, Danni; Zhang, Xianming (Frontiers in Immunology, 2023)
Background Disseminated tuberculosis is an uncommon but devastating form of tuberculosis, possibly developing with the immune response of patients. COVID-19 infection may produce an immunosuppressive effect with possible implications for tuberculosis dissemination.Case Presentation A 17-year-old female with a history of tuberculous pleurisy presented to the hospital with high fever and life-threatening dyspnea after the COVID-19 infection. Her condition deteriorated rapidly with grand mal epilepsy and acute gastrointestinal bleeding with a grossly depressed CD4 T-cell count, which was indicative of her profoundly immunosuppressed state. After identifying Mycobacterium tuberculosis in her cerebrospinal fluid and a subcutaneous abscess in her left lower back, she was diagnosed with disseminated tuberculosis involving both lungs, the central nervous system, the terminal ileum, the liver, bilateral adnexal tissue, and subcutaneous soft tissue in accordance with the chest and abdominal CT. Empirical treatment was initiated with dexamethasone (5 mg/day) and an anti-tuberculosis regimen of isoniazid, rifampicin, pyrazinamide, amikacin, and meropenem, which was replaced with faropenem after she left the hospital. The therapeutic effect was satisfied in the second month of follow-up.We report the first case report of disseminated tuberculosis after COVID-19 infection to the authors' knowledge. Tuberculosis may disseminate and progress during the COVID-19 pandemic, requiring more significant studies to provide better diagnosis and treatment options for the co-infection.